Skrining Tumbuhan Atraktif terhadap Lalat Buah Jantan Bactocera carambolae D&H - Almahdy A; Deddi Prima Putra; Ahsol Hasyim; Mardinus Mardinus (Biota : Jurnal Ilmiah Ilmu-Ilmu Hayati, 2006)
Odour and frequently visited plants by Bactocera sp. were screened for fruit fly attractants. The attractiveness of hexane extracts for B. dorsalis were determined by Y-tube method. Of 20 species treated, 5 species such as Cymbopogon nardus, Ocimum basillicum, Cymbopogon citratus, Cananga odorata, and Hyptis suaveolens showed the attractiveness and the presence of methyl eugenol (ME). These plants could be used as the source of ME for controlling fruit flies infestation. It was also found that Ruta graveolens (Rutaceae) revealed the absence of ME peak by GC-spectrum but responded to fruit flies B. carambolae. The results reveal that the chemical compounds existing in the extracts of R. graveolens may have great potential for development as attractants of the Oriental fruit fly. However, further isolation, identification, and evaluation of active compounds are needed in future studies.